Religious Moderation Education to Counter Radicalism in Students at SMAN 5 Cirebon - Kurnia, Rina; Putri, Anna Shoumilah; Lisnawati, Lia; Nursyifa, Sulistiawati (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2022)
Abstract: The problems discussed in this study regarding religious moderation education to counteract radicalism in adolescents at SMAN 5 Cirebon. This study aims to determine the implementation of religious moderation education at SMAN 5 Cirebon in an effort to ward off radicalism in the educational environment. In addition, this study aims to determine the views or attitudes of students towards religious differences, tolerance, issues of radicalism, and terrorism. The method used in this research is descriptive qualitative method with a field research approach. Data collection techniques used in this study are observation, interviews, and documentation. In this study, researchers conducted field studies to obtain data from research subjects, namely; PAI teachers, counseling teachers, and students of SMAN 5 Cirebon. The result of this study is that students know and understand the attitude that must be taken to ward off radicalism. SMAN 5 Cirebon is also a public school that has implemented religious moderation education in learning activities to increase tolerance among students. Therefore, the attitude shown by students is mutual respect and never discriminates between Muslim and non-Muslim friends. Abstrak: Permasalahan yang dibahas dalam penelitian ini mengenai pendidikan moderasi beragama untuk menangkal radikalisme pada remaja di SMAN 5 Cirebon. Penelitian ini bertujuan untuk mengetahui implementasi pendidikan moderasi beragama di SMAN 5 Cirebon dalam upaya menangkal radikalisme di lingkungan pendidikan. Selain itu, pada penelitian ini bertujuan untuk mengetahui pandangan atau sikap siswa terhadap perbedaan agama, toleransi, isu radikalisme, dan terorisme. Metode yang digunakan dalam penelitian ini yaitu metode kualitatif deskriptif dengan pendekatan studi lapangan. Teknik pengumpulan data yang digunakan dalam penelitian ini yaitu observasi, wawancara, dan dokumentasi. Dalam penelitian ini peneliti melakukan studi lapangan untuk mendapatkan data dari subjek penelitian yakni; Guru PAI, Guru BK, dan siswi SMAN 5 Cirebon. Hasil penelitian ini yaitu siswa mengetahui dan memahami terkait sikap yang harus dilakukan untuk menangkal radikalisme. SMAN 5 Cirebon juga merupakan sekolah umum yang telah menerapkan pendidikan moderasi beragama dalam kegiatan pembelajaran untuk meningkatkan sikap toleransi antar siswa. Oleh karena itu, sikap yang ditunjukkan siswa diantaranya sikap saling menghargai dan tidak pernah membedakan antar teman muslim dan non-muslim.